Knowledge Management Integrated Web-Based Information Security Course Tutoring System - (:unkn) unknown (TEMPUS PUBLICATIONS, 2009)
In this study a model and software package called WebCoach, which operates as a learning content management system (LCMS), has been developed. It is a web based tutoring system that uses knowledge management techniques to convert the tacit knowledge of experienced lecturers and experts into explicit knowledge. The instructional contents, quizzes and assessments, glossary of terms for information security course were prepared, compiled and organized by this tutoring system. They can be used and reused as learning objects to support learning. WebCoach fulfils the requirements for e-learning standards. It has been applied at Istanbul Commerce University within the information security course. Course grades and student questionnaires for two groups of undergraduate computer engineering students were analysed in the course of this study. The control group did not have access of WebCoach, while the same course was taught via WebCoach to the experimental group. The teaching methodology of the control group was based on a classical narrative model. It was observed that the students using WebCoach achieved better results compared with the control group students, for example, 86% of the students were satisfied with the WebCoach system.
Keywords: web-based education; knowledge management; learning content management system; learning objects; tacit knowledge codification and organization